Pelvic re-irradiation using stereotactic ablative radiotherapy (SABR): A systematic review. - Murray, L; Lilley, J; Hawkins, M; Henry, A; Dickinson, P; Sebag-Montefiore, D (Elsevier, 2017)
Background and Purpose To perform a systematic review regarding the use of stereotactic ablative radiotherapy (SABR) for the re-irradiation of recurrent malignant disease within the pelvis, to guide the clinical implementation of this technique. Material and Methods A systematic search strategy was adopted using the MEDLINE, EMBASE and Cochrane Library databases. Results 194 articles were identified, of which 17 were appropriate for inclusion. Studies were small and data largely retrospective. In total, 211 patients are reported to have received pelvic SABR re-irradiation. Dose and fractionation schedules and re-irradiated volumes are highly variable. Little information is provided regarding organ at risk constraints adopted in the re-irradiation setting. Treatment appears well-tolerated overall, with nine grade 3 and six grade 4 toxicities amongst thirteen re-irradiated patients. Local control at one year ranged from 51% to 100%. Symptomatic improvements were also noted. Conclusions For previously irradiated patients with recurrent pelvic disease, SABR re-irradiation could be a feasible intervention for those who otherwise have limited options. Evidence to support this technique is limited but shows initial promise. Based on the available literature, suggestions for a more formal SABR re-irradiation pathway are proposed. Prospective studies and a multidisciplinary approach are required to optimise future treatment.